(untitled) (Experimental biology, 2015)
In this paper we present material to the assessment of the genus Artemisia variety of Ile-Balkhash region. As a result of our investigations it was found that in the family Asteraceae in Ili-Balkhash region in the top of ten genera the first place has Artemisia genus. The distribution of the genus Artemisia is desert of Almaty region. In drawing up the outline of the area of distribution were identified (type area), life form, the period of flowering or fruiting, as well as the locus of the species, which is important for the fees of the genus Artemisia. It is noted that the largest number of species represented perennials (15 species), and the smallest – annuals